2014
DOI: 10.1007/s11626-014-9819-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes

Abstract: Factors influencing porcine oocyte activation were systematically studied. This study included (1) the effect of ionomycin plus various chemical agents on activation, (2) comparison of different electrical activation parameters, (3) optimization of combined activation, and (4) evaluation of the optimized protocols. The results showed that (1) blastocyst rates of ionomycin (Ion) + 6-dimethylaminopurine (6-DMAP) (29.7 ± 1.1%), Ion + cytochalasin B (CB) + cycloheximide (CHX) (29.8 ± 1.2%), Ion + CB + 6-DMAP (30.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…In this study, treatment with 5 μg/mL or 7.5 μg/mL CB produced significantly higher embryonic cleavage and blastocyst rates than those observed in the other groups, which is similar to the results of porcine embryos (Liu et al 2015). The expression levels of the anti-apoptotic gene BCL-XL and the pro-apoptotic genes BAX and CASP3 at the blastocyst stage were lower in CB-treated embryos than in control embryos.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, treatment with 5 μg/mL or 7.5 μg/mL CB produced significantly higher embryonic cleavage and blastocyst rates than those observed in the other groups, which is similar to the results of porcine embryos (Liu et al 2015). The expression levels of the anti-apoptotic gene BCL-XL and the pro-apoptotic genes BAX and CASP3 at the blastocyst stage were lower in CB-treated embryos than in control embryos.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, CB also can be used as a cytoskeletal stabilizer (Dobrinsky 1997). In recent years, CB is being widely used in experimental embryology -for example, CB is commonly used to induce diploid or tetraploid embryos (Tarkowski et al 1977, Somfai et al 2006; can significantly increase the survival rate of frozen embryos (Dobrinsky et al 2000, Dobrinsky 2001; is often used together with other modes of activation to improve embryonic development in mammalian PA (Liu et al 2015); can alleviate the damage caused by the micromanipulation of the embryo and can ensure the chromosome ploidy of the reconstructed embryo in the process of nuclear transfer. However, the effects of CB on the epigenetic modification of porcine parthenogenetically activated embryos have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For electrical activation of rabbit oocytes, voltage field strength, pulse number and duration have interactive effects on the blastocyst development (Escriba & Garcia‐Ximenez, ), and several studies have aimed to optimize these parameters for rabbit oocyte activation (Collas & Robl, ; Livneh et al, ; Onodera & Tsunoda, ; Ozil, ). Our results showed that pulse duration was less important than voltage field strength and pulse number in the parthenogenetic development, which was consistent with previous studies on rabbit and pig oocyte activation (Liu et al, ). In the further experiments, we showed that higher cleavage and blastocyst rates were observed when using multiple pulses and lower voltage field strength, which can be explained by that combination of multiple pluses and low voltage field strength decreased the damage to the oocyte when compared to using higher field voltage strength, and our findings were consistent with previous studies that multiple pulses of electrical activation were beneficial to oocyte activation and embryo development in rabbit, cow, pig and mouse (Collas & Robl, ; Grupen, Nagashima, & Nottle, ; Ozil, ; Vitullo & Ozil, ).…”
Section: Discussionsupporting
confidence: 91%
“…Cytochalasin B (CB) has been shown to inhibit the release of the second polar body after oocytes activation, which can cause diploid development, and it can also prevent embryos fragmentation (Yi & Park, ). Studies have demonstrated that the combination treatment of ION, CHX and 6‐DMAP could efficiently activate porcine and goat oocytes (Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, where knockout models are abundant, it is possible to obtain fertilized blastocysts carrying the desired genotype from transgenic mouse breeders. As validated and characterized transgenic livestock are in limited supply, it is currently necessary to harvest wild-type oocytes, which can be used to generate parthenogenetic embryos through chemical or electrical activation 145,146 . The uncleaved embryos are then genetically engineered through TALEN or CRISPR injections to inactivate the desired gene 11,147 .…”
Section: Barriers and Challenges To Complementationmentioning
confidence: 99%